PJMHS 2023
DOI: 10.53350/pjmhs2023171209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Calcium Hydroxidea and Triple Antibiotic Paste on Inter-Appointment Endodontic Pain

Abstract: Background: Endodontic pain is related to inflammatory reactions in the tissues correlated to the damage, and the nature of damage. Inter-appointment pain is correlated to the instrumentation, irrigation and all the other procedures done during appointments. Triple antibiotic paste can be more effective intacanal medicament than calcium hydroxide. But there was a need to confirm its effectiveness. Aim: To compare the effect of calcium hydroxide and triple antibiotic on inter-appointment endodontic pain. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Numerous meticulously controlled in-vitro and in-vivo studies have shown an intra-canal microbial population reduction or at the very least a suppression of bacterial development. [12][13][14][15] Additionally, calcium hydroxide alters the bacterial cell wall and renders it less antigenic by denatured lipopolysaccharide, a potent endotoxin. A triple antibiotic paste including ciprofloxacin, metronidazole, and minocycline can effectively manage non-vital young permanent teeth and control the root canal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous meticulously controlled in-vitro and in-vivo studies have shown an intra-canal microbial population reduction or at the very least a suppression of bacterial development. [12][13][14][15] Additionally, calcium hydroxide alters the bacterial cell wall and renders it less antigenic by denatured lipopolysaccharide, a potent endotoxin. A triple antibiotic paste including ciprofloxacin, metronidazole, and minocycline can effectively manage non-vital young permanent teeth and control the root canal infection.…”
Section: Discussionmentioning
confidence: 99%